Universidad humanista, científica y democrática paradigma de desarrollo del Perú contemporáneo - Santos Cruz, Teódulo Jenaro (2008)
The Peruvian university is not depositaria of the technological or scientific truth like constituting itself in the axis of the national development, central fact that it motivated the execution of the present investigation. In the historical period of the Spanish coloniaje, as well as in the republican life the University did not have, nor has to the date, own personality like becoming, in the axis of the national development, because she has not formed herself according to our reality and I interest nationals, has not changed the political scheme of the origin of the world-wide university, simply adopted the conception, the method and the government of a millenium ago of years, therefore it is a dehumanized center, in which it prevails the cientificismo and university or been out of phase theories and lacks the democratic advances that must have by their importance in the world-wide society. This historical reality and antecedents justify the removal of its base that entail to change their structures and to form a new being of University, for such reason our problem of raised investigation was: What paradigms must sustain the model of Peruvian university like axis of development of Contemporary Peru? The central variables of the problem are sustained in the approach of the nature of science based on a world-wide vision, in the level of development of Peru and in how altogether creating a scientific attitude in their estates and the population, mainly in the production agents. This scientific conception cannot be to the margin of a variable humanist, that is to say, in as much it is not understood what is man in the Peru and how to honor it in its person, her dignity of such form that humanizes to science and the technology or he is to the service of her the being of the university. The democratic conception completes this theoretical base since at the moment the university is not an island of the society, is not a feudo so that their governed authorities and are muten in brief time, when occupying positions, become scientists, models of government and handle the new monarchy that the estates confer to him; then the democracy has evolved much, but not yet the Peruvian university has arrived. We culminated these approaches conceptualizando the terms: development, legal security, human rights, human person and human dignity. Then, the handled hypothesis necessarily gathers the teorización that we propose to the investigated problem and its presentation like work direction, was formulated thus: “The paradigms that must sustain the university model as axis of development of contemporary Peru is: the humanismo based on the process of hominización, science like instrument of the state and the Peruvian nation and the democracy sustained in a social state of right. ” As far as the material and methods used in the execution of the investigation, there are been premunidos of the conceptions and modern approaches to try at any moment to be objective and to find episteme university that we drew up in the objectives and to obtain to the longed for university paradigm that direccione the development of the Peruvian nation. In the pertinent part to results and discussion, we have found the conception humanist of the man during last the 1000 years and stated that the single Peruvian university makes of it a normative declaration, but is free in all the academic activity, because in his currículo and units of learning do not exist the mini sample of humanismo, on the contrary prohangs to the dehumanization, no university even exhibits certain conception humanist. As far as science, the Peruvian university does not make it and the 30.000 educational college students, approximately, make remedos of scientific research, are mentally ill with the cientificismo, proof of it is that the Peruvian society does not benefit with any from those investigations, inasmuch as they do not enter the scientific or technological market, single are personal rejoicings intrawalls. As far as the democracy, the director, the dean, the institute and director of an institution in general is not but monarchs had with being able and connected among them, who turn to the university their feudo, reason of the struggles and university crisis; this monarchic structure has not changed during last the 500 years of university existence. The conclusions of the thesis are centered in standing out separately on humanismo, science and democracy, the alternative falencias of the Peruvian university, as well as proposals. Finally in this investigation we recommended to carry out matematizadas investigations, of such form that we enter to the era of the accreditation from an historical perspective and in her to postulate the philosophy of this thesis.